2020
DOI: 10.1007/s00228-020-02956-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of azithromycin in pediatrics: a systematic review and meta-analysis

Abstract: Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…In general, due to its broad antibacterial spectrum and safety profile, azithromycin is one of the most commonly prescribed antibacterials in children. In the last two decades, over 700 million doses of MDA-azithromycin have been delivered to children [ 38 ]. However, the safety of azithromycin use in infants is debated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, due to its broad antibacterial spectrum and safety profile, azithromycin is one of the most commonly prescribed antibacterials in children. In the last two decades, over 700 million doses of MDA-azithromycin have been delivered to children [ 38 ]. However, the safety of azithromycin use in infants is debated.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly reported side effects were abdominal pain (53.1%), nausea (21.7%), vomiting (12.8%), and diarrhea (12.5%). However, the prevalence of side effects in the placebo group was not reported [ 38 , 39 ]. In a systematic review of neonates (< 28 days) who received at least one dose of azithromycin, data from 4 RCTs indicated that gastrointestinal side effects were seen in 19.6% of patients [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two other reviews investigated the safety of AZI in children and neonates. The results showed that the safety of different dosage regimens for different indications was variable and the dose was associated with the risk of AEs 40,41 . The development of antibiotic resistance is a concern in childhood asthma using AZI.…”
Section: Discussionmentioning
confidence: 99%
“…In a study (22), the author pointed out that the mediumdosage group (10-30 mg/kg/day) had more adverse events than that of low-dosage group, which implying more dosage would bring more adverse events. In the study (21), single dose 30 mg/kg and 3-day 20-mg/kg/day regimens are well-tolerated, although these new dosages are associated with more adverse effects.…”
Section: Discussionmentioning
confidence: 99%